The use of islamic real estate investment trust (I-REITs) as a contemporary instrument in developing Waqf assets: potential structure, issues and challenges - Hasan, Aznan; Sulaiman, Syahnaz (IIUM Press, 2016)
The primary objective of this paper is to explore the potential of Islamic Real Estate Investment Trusts (I-REITs) as an effective instrument for financing waqf development activities. This study employs legal research methodology, (the data used were largely library-based and documentary in nature), in which opinions of jurists, classical and contemporary are analysed in discussing the potential of I-REITs as a mechanism to develop waqf assets. Besides, several resolutions issued by relevant market authorities are referred to in this study. The study concludes that despite several challenges, with proper implementation, I-REITs may be adopted by a waqf institution as a mechanism to finance the development of their waqf assets. The novelty of this paper lies in the proposed structure of I-REITs, which can be a useful reference for the policy-makers and REITs issuers in establishing an enabling environment within which waqf I-REITs can potentially operate. Therefore, this study hopes to shed some light on the potential of waqf I-REIT to become an asset class to provide diversity for the public to give waqf.